Exploring Intrinsic and Extrinsic Factors Shaping EFL Students’ Speaking Confidence: A Qualitative Study at an Islamic Senior High School in Indonesia - Mohammad Yanser Fathan; Konder Manurung; Zarkiani Hasyim (FOSTER: Journal of English Language Teaching, 2026)
This study explored the intrinsic and extrinsic factors shaping EFL students' speaking confidence at an Islamic senior high school in Indonesia. Using a qualitative descriptive design, data were collected through semi-structured interviews with five eleventh-grade EFL students who were purposively selected based on their varying levels of active participation and speaking ability in English classes. Interview transcripts were analyzed using thematic analysis to identify patterns in factors affecting speaking confidence. The findings revealed five intrinsic factors shaping speaking confidence: (1) self-esteem (moderate to high levels), (2) motivation (integrative and instrumental types), (3) language proficiency (intermediate to advanced self-rated ability), (4) language anxiety (moderate to high levels), and (5) past speaking experiences (positive or negative). Four extrinsic factors emerged: (1) teacher support (encouragement, corrective feedback, patience), (2) peer influence (supportive versus critical responses), (3) classroom atmosphere (competitive versus collaborative), and (4) institutional speaking programs (debate clubs, English days). Students who received consistent positive feedback and supportive peer interactions demonstrated increased willingness to communicate, while those experiencing fear of making mistakes or negative peer responses showed reduced participation. This study contributes to EFL research by providing context-specific insights from an Indonesian Islamic senior high school setting, demonstrating that speaking confidence is dynamically shaped through the interaction between learners' psychological conditions and their learning environment. The findings offer practical implications for EFL educators to create supportive classroom conditions and implement structured speaking opportunities.